Mahindra trucks & bus division : building a marketing plan - Sahay, Arvind, (SAGE Business. Cases., 2019)
Mahindra Trucks and Bus Division (MTBD) of Mahindra & Mahindra is at an interesting stage of its evolution. Having gone through a bad patch with a product that was not quite up to the mark, it appears to have got the product right by early 2018 and truck sales had been going up in the country for the previous four years.